Bearing Capacity of Large Drilled Shafts Fully Embeded in Claystone and Sandstone Layers - Marwaji , Muhammad An Al; Arifin, Yulian Firmana (Civil and Environmental Science Journal (CIVENSE), 2022)
This paper focuses on analyzing the bearing capacity of large diameter drilled shafts that are fully embedded in the claystone and sandstone layers. The foundations used are the drilled shafts for the Pulau Balang bridge pylons built across the Balikpapan bay. Three bored pile foundations with a planned diameter of 2 meters by 60 meters were used. The bearing capacity of the foundation in the field was carried out using the Osterberg cell test. The bearing capacity of the upper side of the foundation is 32.77, 27.26, and 114.46 MN, and the lower parts are 26.98, 27.16, and 50.25 MN, respectively. The results show that the method closest to the upper part of the OC test is the method suggested by Kulhawy and Phoon, with a value of C = 0.5. As for the lower part, the closest approach is the combination of the Kulhawy and Phoon and the Rowe and Armitage methods. The combinations of methods that approximate the total bearing capacity of the field are the Kulhawy and Phoon (1993) and Rowe and Armitage (1987) methods for the dominant claystone layer, and the O'Neil and Reese (1993) and Rowe and Armitage (1987) methods for the main sandstone layer.